2021
DOI: 10.1016/j.gerinurse.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral nutrition supplements in persons with dementia: A systematic review

Abstract: Persons with dementia are at risk of malnutrition, evidenced by low dietary intake, which has consequences for nutritional status, activity of daily living and disease progression. The effects of oral nutrition supplements (ONS) on nutritional intake, nutritional status, and cognitive and physical outcomes in older persons with dementia were evaluated. Methods: PubMed, Medline, Embase, CINAHL and the Cochrane Central Register of Controlled Trials were searched in December 2017, and this was repeated in May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…A high hemoglobin level generally indicates a good trophic condition. Patients maintaining better nutritional status are unlikely to have a risk for aspiration because they are anticipated to intake sufficient nutrition 15 . Indeed, another scale for nutrition, the BMI, did not differ between patients with and without lower lobe-predominant distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A high hemoglobin level generally indicates a good trophic condition. Patients maintaining better nutritional status are unlikely to have a risk for aspiration because they are anticipated to intake sufficient nutrition 15 . Indeed, another scale for nutrition, the BMI, did not differ between patients with and without lower lobe-predominant distribution.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a great interest in diet as a modifiable risk factor for dementia. Until recently, there has been limited evidence to suggest any form of additional dietary supplements play a role in dementia prevention [ 25 28 ] however the recently published LipiDiDiet clinical trial, randomising participants with prodromal Alzheimer’s Disease to Fortasyn Connect (Souvenaid) or placebo, demonstrated promising improvements in cognition, functional outcomes and cerebral atrophy within the intervention group [ 29 ]. Beyond this, there is a shift to explore the role of whole dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…If food intake for nursing home residents is insufficient, oral nutritional supplements (ONS) can be considered to improve total energy, protein and micronutrient intake. There is strong evidence that ONS have a positive effect on nutritional status, body weight and body mass index in older adults 6 . Research suggests no beneficial effect of ONS on survival of disease‐related malnutrition in adults 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that ONS have a positive effect on nutritional status, body weight and body mass index in older adults. 6 Research suggests no beneficial effect of ONS on survival of disease-related malnutrition in adults. 7 A recent systematic review by Tangvik et al 6 reported that, although ONS may improve nutritional status, no effects on functional outcomes were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation